Pendekatan Feminisme dalam Studi Hukum Islam - Wafda Vivid Izziyana (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
The Islamic religion nowadays is demanded to involve actively in giving solutions of various problems faced by the Muslims. One of them is womanhood issues. Women are often positioned in a subordinate position and are less respected. Moreover, it seems having legitimacy from theological doctrines that is supported by patriarchy system. The reaction of imbalance and injustice from patriarchy system therefore results a feminist movement. The demand of Islamic religion role as expected above can be answered while the conception of religion currently uses normative approach, a theology that is provided with other various approaches such as anthropological, sociological, psychological, phenomenology, and feminism. Those various approaches, which are operationally conceptual, can give solutions to occurred problems. The Islamic religion study using feminism approach is expected to bring Islam back as a hospitable religion for women.